PRINSIP KESEIMBANGAN HAK DAN KEWAJIBAN SUAMI ISTRI DAN PENYESUAIANNYA DENGAN BUDAYA LOKAL MENURUT HUKUM ISLAM - Harwis Alimuddin (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2022)
This study reveals the urgency of adjusting the rights and obligations of husband and wife to the local culture by using the principle of impartiality and obligation as a barometer of adjustment. The problem studied is the nature of rights and obligations in Islamic law discourse; local cultural relations with the rights and obligations of husband and wife in sharia texts; and the pattern of application of the principle of impartiality and the obligations of husband and wife. The data collection technique used is a literature study. The data were analyzed using lughawiyyah and istislahiyyah theories. This study concludes that the rights and obligations of husband and wife are not something rigid, but something flexible that can be adapted to local culture while maintaining the principle of equality and the obligations of husband and wife.